2014
DOI: 10.3109/1547691x.2014.899411
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-mediated impairment of macrophageal uptake of environmental TiO2particles to explain inflammatory effect of TiO2on airways during pregnancy

Abstract: Innate defenses against environmental particulate exposures can become deficient when physiological background of the organism is unbalanced. Even those exposures considered innocuous may then become harmful. For example, one of the important inherent risks of pregnancy is increased inflammatory responsiveness in the airways, which extends to exposures considered otherwise innocuous: it has been observed that normally ''inert'' particulates become inflammatory in pregnancy. They lead to enhanced airway inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…In this study, elevated estrogen levels during pregnancy were found to contribute to the resulting asthma risk. (20) Our findings also support that enhanced airway inflammation is due to exposure to inert particles. Consistent with a recent study (15) where an association with powder use and asthma was reported, the relationship between body powder use and respiratory conditions likely reflects an enhanced inflammatory response due to powder use, suggesting a mechanism by which EOC risk is increased.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, elevated estrogen levels during pregnancy were found to contribute to the resulting asthma risk. (20) Our findings also support that enhanced airway inflammation is due to exposure to inert particles. Consistent with a recent study (15) where an association with powder use and asthma was reported, the relationship between body powder use and respiratory conditions likely reflects an enhanced inflammatory response due to powder use, suggesting a mechanism by which EOC risk is increased.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is also consistent with experimental data showing that in the presence of estrogen and/or estrogen and progesterone, the ability of macrophages to clear inert particulates is altered, enhancing the inflammatory response leading to the development of asthma in mouse offspring. (20) It has also been proposed that chronic inflammation, resulting from exposure to body powder, whether through inhalation or through a transvaginal route, may exert a suppressive effect on adaptive immunity, leading to increased risk of EOC. (30) These findings suggest that AA women may be particularly susceptible to exposure to body powder due to having higher endogenous estrogen levels compared to white women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Offspring of mothers exposed to particles developed airway allergy, evidenced by allergic inflammation and airway hyper responsiveness, which was absent in control offspring [131]. The effect of maternal TiO 2 exposure was ascribed to impaired clearance of particles by macrophages and thus a greater inflammatory response in the dams [132]. The latter finding indicates that "inert" particles may become inflammogenic in pregnancy, due to alterations in hormonal balance that subsequently changes regulation of uptake of particles by alveolar macrophages and thus lessens clearance of particles from the maternal lungs.…”
Section: Immune Systemmentioning
confidence: 93%